Pengaruh Media Pembelajaran Visual Diam Terhadap Perkembangan Aspek Kognitif Anak Kelas A Di Tk Gowata Desa Taeng - Musfira; Asyifa Krama, Nurul; Bahri, Aliem (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This study aims to measure the effectiveness of using silent visual learning media in the form of images to enhance the cognitive development of children. This research adopts a quantitative approach using experimental design, specifically a Nonequivalent Control Group Design. The study involved 12 children aged 4–5 years from Class A at TK Gowata, Desa Taeng. Data were collected through treatment tests and observation and analyzed using descriptive and inferential statistics. The findings indicate that learning using silent visual media positively and significantly influences children’s cognitive development. The experimental group demonstrated higher average cognitive development scores compared to the control group. Silent visual media was found to effectively boost children’s enthusiasm, focus, and understanding of learning materials. Hence, this medium serves as an engaging, effective, and enjoyable method for fostering the cognitive development of early childhood learners.